INTERACTIVE TECHNOLOGIES OF PROFESSIONAL LEARNING TRAINERS OF FUTURE HUMANITARIAN TEACHERS SPECIALTIES: PROBLEMS AND PROSPECTS (Pedagogy of Higher and Secondary Education, 2022)
In the article the author describes the role of interactive techniques in the process of raining of future teachers, defines the problems and prospects of their usage at philological departments of higher educational establishments.
Keywords: interactive technologies of training; interactive methods; pedagogical interaction